Sobre práticas pedagógicas em um contexto escolar diferenciado: análises de duas ações do PIBID de Ciências Sociais na escola indígena Tekator. - Andrade, Maurizan Alves de (Universidade Federal do Tocantins, 2019)
Analyze the Institutional Program of Initiatives for Teaching (PIBID), as a project that enables improvements in pedagogical practices, showing its main points of practice and its practical application. This analysis will be done through the works developed within the Campus of Tocantinopolis, through the Social Sciences Course, which works in partnership with schools agreed with the PIBID project. The Social Sciences subproject develops works in partnership with Indigenous schools and urban schools, thus providing an interculturality among the students of the participating schools, the works are developed according to the goals and objectives established by PIBID / UFT, and seeks to do A dialogue through the two cultural realities, on the one hand, demystifying pre-conceived ideas about indigenous peoples from the time of colonization, and which still survive in the midst of the society tocantiopolina, and on the other hand contributing in the valorization of the indigenous cultural heritage, and Collaboration in the construction of the notional culture. The aim of this work is to develop pedagogical projects within the basic education schools, in this case within an indigenous school and an urban school, valuing the cultural diversity existing within each society.